Clarice Bean, that's me - Child, Lauren (Cambridge, Mass. : Candlewick Press, 1999)
A girl describes the hectic life she leads among the members of her large family, and her search for a little peace and quiet.
"First published in Great Britain in 1999 by Orchard Books, London"--P. facing t.p.
Added title page title: This is me Clarice Bean.
Kirkus Review.
Pub Weekly.
School Library Journal.
Kirkus Review, August 1999.
Keywords: Family life -- Fiction; Family life -- Fiction